Expected Credit Loss Modeling from a Top-Down Stress Testing Perspective - Gross, Marco; Laliotis, Dimitrios; Leika, Mindaugas; Lukyantsau, Pavel (Washington, D.C. : International Monetary Fund, 2020)
The objective of this paper is to present an integrated tool suite for IFRS 9- and CECL-compatible estimation in top-down solvency stress tests. The tool suite serves as an illustration for institutions wishing to include accounting-based approaches for credit risk modeling in top-down stress tests. The tool suite is made available online along with this paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Accounting and Auditing; Financial Institutions and Services